2018
DOI: 10.1155/2018/6982014
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Methylene Blue and Crystal Violet onto Micro-Mesoporous Zr3O/Activated Carbon Composite: A Joint Experimental and Statistical Modeling Considerations

Abstract: Zirconium oxide/activated carbon (Zr3O/AC) composite was synthesized to remove methylene blue (MB) and crystal violet (CV) from the aqueous medium. The Zr3O/AC sample was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analyses (EDS), Raman spectroscopy (RS), BET surface area, and Fourier transform infrared spectroscopy (FTIR). XRD profiles confirmed the successful synthesis of the zirconium oxide/activated carbon composite. SEM images showed multideveloped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…ANOVA analysis (Table 2S †) was utilized in this work to determine the adequacy of the predicted model. 97,98 Therefore, 'P-value' less than 0.05 infer that designed models were significant for both ketoprofen and aspirin. The correlation coefficient (R 2 ) and the adjusted correlation coefficient (R Adj 2 ) were close to 0.99 for both ketoprofen and aspirin systems, showing the existence of a good correlation between data.…”
Section: Optimization Using Response Surface Approachmentioning
confidence: 99%
“…ANOVA analysis (Table 2S †) was utilized in this work to determine the adequacy of the predicted model. 97,98 Therefore, 'P-value' less than 0.05 infer that designed models were significant for both ketoprofen and aspirin. The correlation coefficient (R 2 ) and the adjusted correlation coefficient (R Adj 2 ) were close to 0.99 for both ketoprofen and aspirin systems, showing the existence of a good correlation between data.…”
Section: Optimization Using Response Surface Approachmentioning
confidence: 99%
“…7a). Aer 5 cycles, the performance sorption decreased from: 65 99.52% / 97.16%, 95.86% / 94.30% and 93.45% / 92.01% for SA, Nap, and Keto molecules, respectively. The sorption regeneration test revealed that the Fe 2 O 3 /biochar could be effectively used as a promising adsorbent for SA, Nap, and Keto nonsteroidal molecules adsorption from aqueous solutions.…”
Section: Renewability Mechanism and Thermodynamic Behaviormentioning
confidence: 97%
“…Renewability is an important factor to evaluate the adsorbent pollutants adsorption. 64,65 The Fe 2 O 3 /biochar regenerated was investigated using ethanol for 4 hours of stirring. The sorption regeneration was repeated 5 times for SA, Nap, and Keto molecules (Fig.…”
Section: Renewability Mechanism and Thermodynamic Behaviormentioning
confidence: 99%
“…In this part of work, response surface methodology technique was used to optimize the adsorption process of Pb 2+ and p-nitrophenol in order to modelled the reaction pathways taking into account the inuence of different parameters as a function of lead and p-nitrophenol removal efficiency onto BC-500. 88,89 Therefore, the analysis of variance results (ANOVA) for lead or p-nitrophenol adsorption were presented in Table 10. Based on this statically analysis we conclude that: The term 'P-value' less than 0.05 implies that designed model is signicant for both lead or p-nitrophenol.…”
Section: Langmuir Isothermmentioning
confidence: 99%